Optimization of Inspired Oxygen during Mechanical Ventilation (OPTI-OXYGEN): rationale and design of a pragmatic randomised controlled trial - Taylor B Thompson; Todd W Rice; Guy N Brock; Jonathan Peters; Elliott D Crouser; Matthew Exline; Sonal R Pannu; Jamie Zimmer; Jeffrey C Horowitz (BMJ Open)
Introduction Targeted oxygenation protocols in mechanically ventilated patients are critical in avoiding the deleterious effects of hypoxaemia and hyperoxaemia. Peripheral oxygen saturation (SpO2) is a practical metric that commonly drives oxygen titration protocols and guidelines but has inaccuracies attributable to patient variability that can lead to occult hypoxaemia. Conversely, arterial oxygen saturation (SaO2) offers accuracy but is costly and invasive. We aim to develop a novel approach to targeted oxygenation that collectively uses the accuracy of SaO2 and the feasibility of SpO2 to mitigate occult hypoxaemia and prevent hyperoxaemia.Methods and analysis The Optimization of Inspired Oxygen during Mechanical Ventilation trial is a pragmatic stepped wedge, open label, cluster-randomised controlled trial of an algorithm-based SpO2-SaO2 electronic alert-based oxygen titration protocol. The intervention arm includes targeted oxygenation via an electronic SpO2-SaO2 driven alert protocol. The control group will be subjected to oxygen titration according to standard practice. Within the intervention arm, patients will be assigned to groups with different SpO2 targets based on the degree of SpO2-SaO2 difference. In the ‘Conserve O2’ group, where SpO2<SaO2 by 1–5% or SpO2>SaO2 by 1–2%, electronic alerts will be used to titrate FiO2 to a target SpO2 of 90–94%. In the ‘Boosted O2’ group, where SpO2>SaO2 by 3–5%, electronic alerts will be used to titrate FiO2 to a target SpO2 of 93–97%. Patients with an SpO2-SaO2 difference >5% in either direction will be monitored but not assigned to either group. The sample size to determine efficacy is 1620 subjects, randomised over 60 weeks. The primary outcome is the proportion of time during mechanical ventilation spent within the target range, SpO2 of 90–94% (Conserve O2) or SpO2 of 93–97% (Boosted O2) at any FiO2. Secondary outcomes include the proportion of time with SpO2 >94% or SpO2 >97% with FiO2 ≤0.4 within each respective algorithm, the proportion of time with SpO2 <90% or SpO2 <93% within each respective algorithm, length of intensive care unit and hospital stay, hospital mortality, ventilator and vasopressor free days, new onset of arrhythmia when SpO2 <90%, and change to comfort care status (DNRCC) and time to DNRCC after enrolment.Ethics and dissemination The protocol was approved by The Ohio State University Institutional Review Board (Protocol # 2023H0016) and is registered at ClinicalTrials.gov (NCT 05923853). Progress and safety of the trial are monitored by an independent Data and Safety Monitoring Board. Study results will be published in peer-reviewed medical journals. This study is being carried out with a waiver of consent as participation in the study presents no more than minimal incremental risk compared with routine clinical care for mechanically ventilated critically ill adults outside of the study.Trial registration number NCT05923853.